ANALYSIS OF SATISFACTION WITH PHYSICAL FITNESS AND WELLNESS SERVICES PROVIDED IN THE UNIVERSITY SPORTS CENTER AMONG UNIVERSITY STUDENTS (Physical Culture and Sport: Scientific Perspective, 2025)
The article presents the results of a study involving 172 university students aged 18 to 25, aimed at analyzing their satisfaction with physical fitness and wellness services (PFWS) and exploring sex-related and behavioral differences based on the frequency of visiting a sports and wellness center (SWC). The participants were divided into two groups according to their attendance frequency: Group 1 (n=95) attended fitness classes three or more times a week; Group 2 (n=77) – one to two times a week. The data were collected during martial law, a factor significantly influencing students' physical and psycho-emotional states. The SQAS (Service Quality Assessment Scale), adapted for wartime conditions, was used to assess PFWS satisfaction. The final questionnaire included 42 items grouped into 7 factors. The scale demonstrated high reliability (Cronbach's alpha = 0.991, split-half reliability = 0.994). Statistical analysis revealed that satisfaction with PFWS was not significantly influenced by sex, time of day, or service type preferences. However, students who visited the SWC more frequently rated the facilities and safety significantly higher (p < 0.05) and reported overall greater satisfaction with the services. A strong correlation (p < 0.05) was found between various PFWS satisfaction factors and quality of life indicators, such as physical functioning, general health, vitality, and social functioning. The level of satisfaction with PFWS did not show statistically significant differences based on sex, duration of visits to the SWC, preferred type of service, or the time of day students attended the SWC. However, a statistically significant relationship was found between the level of satisfaction with PFWS and the frequency of SWC visits: students who exercised more frequently gave higher ratings for the safety and quality of the facilities. These findings highlight the role of regular physical activity in supporting students’ well-being, especially in stressful conditions. The results can be used to improve the organization of SWC services and promote student engagement in physical activity during crises.
Keywords: students; sports club; physical fitness and wellness services; quality; higher education institution; sports infrastructure